Thermophysical aspects of magnetized Williamson fluid flow subject to both porous and non-porous surfaces: A Lie symmetry analysis - Khalil Ur Rehman; Wasfi Shatanawi; Kamaleldin Abodayeh (Case Studies in Thermal Engineering, 2021)
The present outcomes on thermally magnetized flow fields by way of symmetry analysis will assist the research community to examine fluid dynamics, particular structures of fluids, and their interaction with the homogeneous porous mediums. The new scaling group of transformations is offered rather than using so-called transformations from existing literature to better narrate the thermal fluid interaction with the porous magnetized medium. Symmetry analysis is carried to find the physical quantities at the surface by executing (i) Slip and non-Slip flow fields (ii) Porous and non-porous mediums (iii) Magnetized and non-Magnetized flow fields. Such collective physical effects result in a complicated mathematical differential system. For the solution purpose firstly the concerned scaling group of transformations is obtained by using symmetry analysis and such transformations are used to covert the differential system into an ordinary differential system. The ultimate differential system is solved by using the shooting method along with RK scheme. The observations are shared with the help of line graph study and tabular forms. It is concluded that for the porous and non-porous mediums, resistance towards fluid declines as the Weissenberg number enhances whereas the heat transfer normal to both porous and non-porous surfaces increases as thermal diffusivity declines.